Development of Mobile Learning with a STEM Approach in Physics Learning at SMA YP IPPI - Asmiliyah, Asmiliyah; Khaerudin, Khaerudin; Solihatin, Etin (Journal of Education Research and Evaluation, 2021)
Senior High School (SMA) is a secondary education level that prioritizes the preparation of students to continue higher education with specialization. The realization of this specialization has been carried out from class X with three specialization programs, namely a specialization in Social Sciences (IPS), a specialization in Mathematics and Natural Sciences (MIPA). Physics is one of the characteristics of the subject of the Mathematics and Natural Sciences specialization program which aims to make students have the ability to master concepts, principles of physics and develop thinking skills that are useful for solving problems in everyday life. This research was conducted in class XI MIPA at SMA YP IPPI having its address at Jalan Petojo Barat III / 2, Central Jakarta. The research will be carried out for 7 months, from January to July 2021. This research is a research and development study using the Alessi and Trollip model developed by Stephen M. Alessi and Stanley R. Trollip dan model waterfall by Sommerville Ian. The model consists of three stages of development, namely planning, design and development. The waterfall model is combined at the development stage. Combining the STEM approach and problem-based learning models with mobile learning can be one of the lessons that is suitable for generations. The results of these studies indicate that the development of cross platform mobile learning application with the STEM approach is effective in learning physics.